Modificarea comportamentului de consum al populației din perspectivă ecologică, în țările Uniunii Europene - Humă, Cristina (Calitatea Vieții, 2013)
The paper highlights changes in consumer behaviour of population in recent years, in EU countries, from the perspective of sustainable consumption, by adopting a healthy consumption of food, by lower energy consumption in households, by rational use of water resources and by minimizing waste generated in households. In this respect, it was used the statistical analysis, which revealed that there are some positive signs of the change in consumer behaviour, in the sense of sustainability. Thus, in terms of food consumption, it was found that aspects of the human health and the environment have made the interest for organic food to grow. As a result of increasing demand for organic food, organic agricultural area, increased in most EU member states, including Romania. For the energy consumption of households, the analysis revealed that, at the level of EU, renewable energy use has become increasingly, our country recorded one of the highest increase in the field of alternative energy. Regarding the generation of waste at the household level, there has been a decrease in their quantity in the EU, which was also felt in Romania. In addition, there has been an increasing amount of waste recycled in almost all EU countries, while in our country it has been reported a decline. The study also refers to other relevant issue, namely, the European citizens attitude towards the impact that their consumption habits have on the environment and the measures they have taken to reduce this impact. The analysis of Eurobarometer data (Attitudes of European citizens towards the environment) shows a higher awareness, in recent years, of environmental issues associated with consumer habits, and a positive behaviour of European citizens in the use of resources, by adopting measures to improve their efficiency of using them.